Effect of Exemplar of Wettli On Acquiring Grammatical Concepts Among Basic 7th Class Female Students in Kurdish Language Grammar (Journal Of Educational and Psychological Researches, 2016)
The current paper aims at knowing the effect of  Exemplar of Wettli On Acquiring Grammatical Concepts Among Basic 7th Class Female Students in Kurdish Language Grammar. The current paper is confined to a sample of  Basic 7th Class Female Students-  Khaniqin –belonged Morning schools for the academic year 2014-2015 . The sample amounted 50 female students  distributed on two sections ( A,B) . Section A represented  experimental group ( 24) female  students  studied according to the exemplar of ( Wettli) and (B) represented control group (26) female students who have studied with traditional method. The researcher has qualified between these two groups  based on coefficients ( age, intelligence,  marks of the first course).  The scientific subject has been determined by  many grammars subjects in the book (( Zaman Waa Dah Bi Kurish) decided to be studied in basic 7th class. The researcher has formed behavior goals  and has prepared  teaching plans  sufficient for these two groups; she has also prepared a test to acquire  grammatical concepts  , composing of  30 items by which the teacher has taught  the two groups. By the end of the experience,  tool of  research has been applied  on students of both groups. After analyzing the result statistically by using T-test  for the two independent samples , the results have indicated the progress of experimental group studying Grammar Subject according to the method of ((Wettli))  over the control one.  The researcher has placed  a set of recommendations and suggestions that are valid for research.